2015
DOI: 10.1016/j.ultrasmedbio.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Microvascular Tortuosity during Tumor Evolution Using Acoustic Angiography

Abstract: The recent design of ultra-broadband, multi-frequency ultrasound transducers has enabled high sensitivity, high-resolution contrast imaging, with very efficient suppression of tissue background using a technique called acoustic angiography. Here we perform the first application of acoustic angiography to evolving tumors in mice predisposed to develop mammary carcinoma, with the intent of visualizing and quantifying angiogenesis progression associated with tumor growth. Metrics compared include vascular density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 41 publications
3
85
0
Order By: Relevance
“…Recent acoustic angiography studies have characterized the tortuosity of tumor vasculature and found it to be significantly higher than that of control tissue [5, 6]. However the presence of a tumor and its effect on the 3-D morphology and spatial variability of surrounding vasculature has not yet been characterized quantitatively using ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Recent acoustic angiography studies have characterized the tortuosity of tumor vasculature and found it to be significantly higher than that of control tissue [5, 6]. However the presence of a tumor and its effect on the 3-D morphology and spatial variability of surrounding vasculature has not yet been characterized quantitatively using ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…By mechanically scanning this dual-frequency transducer, it is possible to acquire high resolution images of vasculature (Fig. 1) and differentiate healthy tissue from tumor-bearing tissue based on visualizing angiogenesis (Gessner et al 2012; Shelton et al In review). However, the exact mechanism by which broadband harmonic energy is produced is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of a lower transmit frequency allows for excitation of microbubbles closer to their resonance frequencies and provides better penetration relative to high frequency imaging. Using this approach, which we refer to as “acoustic angiography,” we have demonstrated the ability to differentiate healthy from tumor-bearing tissue based on quantitative, image-based metrics of angiogenesis (Gessner et al 2012; Shelton et al 2015). Figure 1 shows example acoustic angiography maximum intensity projections of tortuous vasculature associated with a subcutaneous tumor model, along with anatomical B-mode images of the same tissue volume.…”
Section: Introductionmentioning
confidence: 99%